2010
DOI: 10.1242/dev.042101
|View full text |Cite
|
Sign up to set email alerts
|

Sequential requirement of Sox4 and Sox11 during development of the sympathetic nervous system

Abstract: SUMMARYThe highly related transcription factors Sox4 and Sox11 are expressed in the developing sympathetic nervous system. In the mouse, Sox11 appears first, whereas Sox4 is prevalent later. Using mouse mutagenesis and overexpression strategies in chicken, we studied the role of both SoxC proteins in this tissue. Neither Sox4 nor Sox11 predominantly functioned by promoting pan-neuronal or noradrenergic differentiation of sympathetic neurons as might have been expected from studies in neuronal precursors of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 51 publications
6
110
1
Order By: Relevance
“…Ablation of both factors greatly reduced the survival of neural and mesenchymal progenitor cells during organogenesis (17), as well as of neuron progenitor cells during the spinal cord development (22). While Sox11 was reported to play an indispensable role in the proliferation of tyrosine hydroxylase expressing cells at early stages, Sox4 is crucial to their survival at late stages (21). Further lines of evidence demonstrate that Sox11 also helps improve the survival of differentiated post-mitotic sensory neurons (19).…”
Section: Discussionmentioning
confidence: 99%
“…Ablation of both factors greatly reduced the survival of neural and mesenchymal progenitor cells during organogenesis (17), as well as of neuron progenitor cells during the spinal cord development (22). While Sox11 was reported to play an indispensable role in the proliferation of tyrosine hydroxylase expressing cells at early stages, Sox4 is crucial to their survival at late stages (21). Further lines of evidence demonstrate that Sox11 also helps improve the survival of differentiated post-mitotic sensory neurons (19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that SoxC family members have overlapping expression patterns and molecular properties (Dy et al, 2008). Sox4 and Sox11 have both been implicated in cardiac and neuronal development, whereas Sox12 appears redundant (Bergsland et al, 2006;Hoser et al, 2008;Bhattaram et al, 2010;Potzner et al, 2010). As C-terminal domains of other Sox family members diverge from SoxC family members, protea-somal regulation of Sox proteins appears confined to the SoxC family.…”
Section: Discussionmentioning
confidence: 99%
“…SoxC proteins are also important for development of the sympathetic nervous system (Potzner et al, 2010). In the sympathetic ganglia, Sox11 is predominantly expressed in actively dividing neural progenitors and not so much in postmitotic cells; while in DRG and TG, Sox11 is predominantly expressed in postmitotic neurons but not in dividing cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, overexpression of Sox11 promotes neuronal maturation in the developing chick neural tube (Bergsland et al, 2006). In the PNS, a recent report showed that Sox4 and Sox11 are required for sympathetic neuron development (Potzner et al, 2010). We are particularly interested in Sox11, whose expression is the most robust in the nervous system.…”
Section: Introductionmentioning
confidence: 99%